Pengaruh Pemberian Sinbiotik, Probiotik, dan Prebiotik terhadap Depresi, Stres, dan Mood pada Orang Dewasa: Systematic Review dan Meta-Analisis: Effects of Synbiotic, Probiotic, and Prebiotic Supplementation on Depression, Stress, and Mood in Adults: A Systematic Review and Meta-Analysis - Habibi, Nur Ahmad; Gusnedi, Gusnedi; Nindrea, Ricvan Dana; Hasniyati, Rina; Afriza, Renita; Rusydi, Riska; Yuska, Defniwita; Darningsih, Sri; Zulkifli, Zulkifli; Ismanilda, Ismanilda; Handayani, Marni; Utami, Citra Tristi; Umar, Hermita Bus; Dwiyanti, Defriani; Yuniritha, Eva (Universitas Airlangga, 2025)
Background: Psychobiotics, including probiotics, prebiotics, and synbiotics, have been proposed to improve mental health through modulation of the gut–brain axis. However, findings from randomized controlled trials (RCTs) remain inconsistent, Objectives: To systematically review and synthesize evidence on the effects of probiotics, prebiotics, and synbiotics on depression, stress, and mood in adult populations. Methods: A comprehensive search was conducted in PubMed, yielding 531 articles, of which 14 RCTs met the inclusion criteria. Risk of bias was assessed using the Cochrane Risk of Bias Tool. Meta-analyses were performed using both fixed- and random-effects models in RevMan. The study protocol was registered in PROSPERO (CRD420251103338). Discussions: Ten RCTs (n = 881) assessing depression did not show consistent benefits (SMD = –0.72; 95% CI: –1.42 to –0.01; p-value = 0.05; I² = 96%). Six RCTs (n = 444) evaluating stress also showed non-significant effects (MD = –1.35; 95% CI: –3.70 to 1.01; p-value = 0.26; I² = 73%). Conversely, six RCTs (n = 376) demonstrated significant improvements in mood (MD = 0.73; 95% CI: 0.25 to 1.20; p-value = 0.003; I² = 75%). Meta-regression indicated that larger sample sizes were associated with more consistent improvements in mood (p-value = 0.04). Sensitivity analyses confirmed the stability of the findings, and no evidence of publication bias was detected. Conclusions: Probiotic, prebiotic, and synbiotic supplementation may provide beneficial effects on mood and could serve as a potential nutritional intervention to enhance psychological health. However, effects on depression and stress inconsistent.